Entre o processo de constitucionalização e o racismo estrutural: a participação das negras e dos negros na construção do poder constituinte originário na Assembleia Nacional Constituinte de 1987/1988 - Olívia Maria Silva Felício (2023)
This research aims to recover the participation of black men and women in the National Constituent Assembly and the essentiality for the guarantee of their social rights, among them mainly the rights of equality and freedom. Rescuing the context of struggle for recognition of rights and visibility becomes necessary to demystify narratives that can strategically make invisible the social movements that were present there. In addition to demonstrating the course during and after the constituent, unveiling the legislative effectiveness and how society articulates structural racism. That is, at first considering the concepts of the modern constitution, constitutional openness, identity of the constitutional subject and their correlation with racial rights. Pervading the essential concepts of race and racism, and mainly presenting the line of reasoning of race as a social demarcator. Throughout this work, we also reinforce the meaning of racial democracy and how this, although in several discourses considered official, is highlighted as such, it is not a Brazilian characteristic. A country that daily denotes its racist traits in all social sectors due to its inability to recognize racism as a strategic tool of segregation. Finally, the trajectory for the conquest of the labor rights of maids, the social indicators of this working class and the narrative in dispute until the enactment of PEC 72/2013 are also rescued.